2015
DOI: 10.1177/1356336x15605519
|View full text |Cite
|
Sign up to set email alerts
|

The impact of occupational socialization on physical education pre-service teachers’ beliefs about four important curricular outcomes

Abstract: Most national Physical Education (PE) curriculums worldwide are based on a variety of outcome goals. The most important are physical activity and fitness, self-actualization, motor skill development and social development. Capturing PE Teacher Education pre-service teachers' beliefs toward these outcomes may offer a useful insight into the process of identifying and understanding prospective teachers' decisions and actions. The aim of the current study was to compare PE pre-service teachers' beliefs regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 42 publications
2
31
1
1
Order By: Relevance
“…No "wash out" effect was evident during the organizational socialization. These results are not in line with previous research on this persistent problem for newly qualified teachers (Schempp et al, 1993) and the low influence of TE (Adamakis & Zounhia, 2016;Morgan & Hansen, 2008). While Capel et al (2011) argued that teachers tend to reject what they have learned during TE and return to the methods with which they were familiar during their own schooling, these three teachers implemented what they had learned such as TGfU, Sport Education, use of feedback, high student activity, individually adapted instruction and games played with small teams.…”
Section: Organizational Socializationcontrasting
confidence: 55%
See 1 more Smart Citation
“…No "wash out" effect was evident during the organizational socialization. These results are not in line with previous research on this persistent problem for newly qualified teachers (Schempp et al, 1993) and the low influence of TE (Adamakis & Zounhia, 2016;Morgan & Hansen, 2008). While Capel et al (2011) argued that teachers tend to reject what they have learned during TE and return to the methods with which they were familiar during their own schooling, these three teachers implemented what they had learned such as TGfU, Sport Education, use of feedback, high student activity, individually adapted instruction and games played with small teams.…”
Section: Organizational Socializationcontrasting
confidence: 55%
“…Although research has shown that teachers' previous experience has a stronger influence than formal TE itself (Adamakis & Zounhia, 2016;Capel et al, 2011;Elliot et al, 2013;Flory & McCaughtry, 2014;Morgan & Hansen, 2008), this was not the case for Tom, Nicole and Amanda. Our results support researchers reporting that TE can contribute to a deeper understanding of PE as a school subject and its relevance and significance for all children (Hemphill et al, 2015;Ingersoll et al, 2014;.…”
Section: Professional Socializationmentioning
confidence: 85%
“…Since PSTs will mostly interact with other students with similar experiences and perceptions during the professional socialization phases, it is possible that these embodied perceptions will not be challenged and instead be reinforced (cf. Adamakis and Zounhia 2016). This may limit the potential influence of PETE and fail to prepare PSTs for their future profession, where they will have to deal with pupils from a large variety of backgrounds and experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, McCullick et al (2012) and Richards, Templin, and Graber (2014), among others, indicate the need for new studies on teacher socialization that illuminate the new conditions. In addition, Adamakis and Zounhia (2016) and Pike and Fletcher (2014) conclude that most studies on socialization of PE PSTs have been qualitative with a lack of longitudinal perspective, and they highlight the urgent need for quantitative studies. This study contributes to the research field through a longitudinal quantitative study conducted in the Swedish context.…”
Section: Knowledge Learned From Teacher Socialization Researchmentioning
confidence: 99%
“…The occupational socialization framework (Lawson, 1986) has been used extensively to identify how Physical Education (PE) (student) teachers view and teach the subject (see, for example, Adamakis and Zounhia, 2015;Hemphill et al, 2015;Meek and CurtnerSmith, 2004;Richards and Templin, 2011;Sutherland and Stuhr, 2012;Zmundy, Curtner-Smith and Steffen, 2009). Examining teachers' childhood involvement in PE and sport, their higher education experiences and the influence of the workplace has allowed researchers to identify what factors influence their teaching.…”
Section: Introductionmentioning
confidence: 99%